1998
DOI: 10.1159/000023904
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Histamine Receptors in Nasal Epithelial Cells and Endothelial Cells – The Effects of Sex Hormones

Abstract: Background: Hyperreactivity of the nasal mucosa is a characteristic of nasal allergy. During pregnancy, aggravation of nasal allergic symptoms is occasionally observed in subjects with nasal allergy. Methods: Using the reverse transcription-polymerase chain reaction and Southern blot hybridization method, we investigated histamine H1 receptor mRNA (H1R mRNA) expressions in specimens of nasal epithelial layer obtained by scraping, as well as cultured human nasal epithelial cells (HNECs) and human mucosal microv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 23 publications
2
47
0
3
Order By: Relevance
“…We also reported that the H1R mRNA level in TDI rats was significantly higher than that of control animals (13). These findings were in line with studies in which the expression of H1R mRNA was increased in epithelial and endothelial cells of nasal mucosa (14), in neural cells (15), and in the nasal scrapings from patients with nasal allergy (4). It has also been reported that H1R binding activity in the nasal mucosa is increased with the development of nasal allergy (16).…”
Section: Discussionsupporting
confidence: 90%
“…We also reported that the H1R mRNA level in TDI rats was significantly higher than that of control animals (13). These findings were in line with studies in which the expression of H1R mRNA was increased in epithelial and endothelial cells of nasal mucosa (14), in neural cells (15), and in the nasal scrapings from patients with nasal allergy (4). It has also been reported that H1R binding activity in the nasal mucosa is increased with the development of nasal allergy (16).…”
Section: Discussionsupporting
confidence: 90%
“…This finding led to a working hypothesis of the existence of a detrimental circuit between histamine and H1R in which histamine-induced up-regulation of H1R gene expression results in an increase in the amount of H1R protein, and this makes the cells more sensitive to histamine and may actually exacerbate the allergic symptoms. It was reported that expression of H1R mRNA was increased in epithelial, endothelial, and neural cells on the nasal mucosa in the patients with occupational rhinitis (34,35). Up-regulation of H1R was also observed in patients with allergic rhinitis (6, 7).…”
Section: Discussionmentioning
confidence: 98%
“…Expression of H1R mRNA is reported to increase in epithelial, endothelial, and neural cells on the nasal mucosa in the patients with occupational rhinitis (46,47). H1R binding activity in the nasal mucosa is also reported to increase during development of nasal allergy (48).…”
Section: Discussionmentioning
confidence: 99%